Pengaruh Kombinasi Pemberian Jus Jambu Biji Merah dan Madu Terhadap Kadar Hemoglobin Ibu hamil - Suryani, Suryani; Kusmaryati, Pauline; Irbawati, Marlita; Suryanti, Yuli (NHM PRESS, 2024)
The prevalence of pregnant women at risk of developing anemia with iron deficiency is around 35-75%, and increases with increasing gestational age. One fruit that can increase hemoglobin levels is guava. The combination of guava contains amino acids (tryptophan, lysine), calcium, phosphorus, iron, sulfur, vitamin A, vitamin B1 and vitamin C. This study aims to determine the effect of the combination of giving red guava juice and honey on maternal hemoglobin levels. pregnant at the Payo Selincah Community Health Center, Jambi City. This research is a quantitative research using the research design